Development of Mathematics Student Worksheets Based on Problem Based Learning in The Topic of Composition Function - Malinda, Anik Putri; Nisa, Roisatun (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
Composition function material is one of the mathematics learning materials that is considered difficult, so the learning process can include problems in everyday life. One solution to overcome these difficulties is the existence of teaching materials in the form of mathematics worksheets which can help students' learning process. This research aims to determine the stages of development and to determine the validity and practicality of mathematics worksheets based on Problem Based Learning material on composition functions. This type of research is development research with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The research instruments used in this study were (1) interview guide (2) validation sheet (3) student response questionnaire. The validation results from two material experts and two media experts obtained an overall average score of 3.4 and 3.8 and met the very good criteria. The practical aspect based on the student questionnaire response criteria is very good with a score of 4.4. From these data, it can be concluded that the Mathematics Student Worksheet based on Problem Based Learning (PBL) composition function material that was developed meets the valid and effective categories so it is suitable for use in the learning process.